Protective effects of transient glucose exposure in adult C. elegans - Murillo, Katharina; Samigullin, Azat; Humpert, Per Magnus; Fleming, Thomas; Özer, Kübra; Schlotterer, Andrea; Hammes, Hans-Peter; Morcos, Michael (Antioxidants, 2022)
C. elegans are used to study molecular pathways, linking high glucose levels (HG) to diabetic complications. Persistent exposure of C. elegans to a HG environment induces the mitochondrial formation of reactive oxygen species (ROS) and advanced glycation endproducts (AGEs), leading to neuronal damage and decreased lifespan. Studies suggest that transient high glucose exposure (TGE) exerts different effects than persistent exposure. Thus, the effects of TGE on ROS, AGE-formation and life span were studied in C. elegans. Four-day TGE (400 mM) as compared to controls (0mM) showed a persistent increase of ROS (4-days 286 ± 40 RLUs vs. control 187 ± 23 RLUs) without increased formation of AGEs. TGE increased body motility (1-day 0.14 ± 0.02; 4-days 0.15 ± 0.01; 6-days 0.16 ± 0.02 vs. control 0.10 ± 0.02 in mm/s), and bending angle (1-day 17.7 ± 1.55; 3-days 18.7 ± 1.39; 6-days 20.3 ± 0.61 vs. control 15.3 ± 1.63 in degree/s) as signs of neuronal damage. Lifespan was increased by 27% (21 ± 2.4 days) after one-day TGE, 34% (22 ± 1.2 days) after four-days TGE, and 26% (21 ± 1.4 days) after six-days TGE vs. control (16 ± 1.3 days). These experiments suggest that TGE in C. elegans has positive effects on life span and neuronal function, associated with mildly increased ROS-formation. From the perspective of metabolic memory, hormetic effects outweighed the detrimental effects of a HG environment.